Exercise in Pregnancy: It’s Effect on Maternal and Fetal Health an Evidence Based Findings - Darshandhari Kapali, Gayatri (Journal of Nursing Education of Nepal, 2022)
Introduction: Exercise in pregnancy is one of the important contributors which also has a direct link between healthy mothers and healthy fetus. The purpose of this study is to review the published articles and recommend the information regarding benefit of exercise in pregnancy on maternal and fetal health.Methods: Systematic search of peer- review publications had been done through Google Scholar, Medline, Pubmed and Scopus. Among the 32 relevant articles on this topic has been selected and reviewed ,analyzed and significant findings have been concluded. Pregnant mothers who do not have obstetric or medical contraindications should be encouraged to exercise during pregnancy. Observational studies of women who exercise during pregnancy have shown benefits such as decreased gestational diabetes mellitus, cesarean birth and operative vaginal delivery. It is related with the course of a healthy pregnancy, since it can increase physical fitness, lower the risk of excessive gestational weight gain, gestational diabetes, pre-eclampsia, macrosomia, and stillbirth. Exercises during pregnancy advances neuro-behavioral relaxation in the fetus.Conclusion: Regular exercise is are recommended for pregnant women, for overall health benefits of maternal and fetal health. Evidences supported that moderate level exercise during pregnancy is safe for the fetus during intra uterine life.
Keywords: Benefit; exercise; maternal and fetal health